2010
DOI: 10.1167/iovs.09-4089
|View full text |Cite
|
Sign up to set email alerts
|

Protection of the Retina by Rapid Diffusion of Hydrogen: Administration of Hydrogen-Loaded Eye Drops in Retinal Ischemia–Reperfusion Injury

Abstract: H(2) has no known toxic effects on the human body. Thus, the results suggest that H(2)-loaded eye drops are a highly useful neuroprotective and antioxidative therapeutic treatment for acute retinal I/R injury.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
101
0
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 153 publications
(111 citation statements)
references
References 33 publications
7
101
0
3
Order By: Relevance
“…At present, similar to the research in animals and clinical trials (Ohsawa et al, 2007;Oharazawa et al, 2010), the use of exogenous HRW presented a powerful research approach to investigate the biological significance of H 2 . This approach was also supported by the fact that exogenous application of 100% saturated HRW (1.56 mL L 21 H 2 in MES buffer) not only triggered Arabidopsis stomatal closure (Col-0; Fig.…”
Section: Gork Acts As the Downstream Target Of Hrw Signalingmentioning
confidence: 99%
See 1 more Smart Citation
“…At present, similar to the research in animals and clinical trials (Ohsawa et al, 2007;Oharazawa et al, 2010), the use of exogenous HRW presented a powerful research approach to investigate the biological significance of H 2 . This approach was also supported by the fact that exogenous application of 100% saturated HRW (1.56 mL L 21 H 2 in MES buffer) not only triggered Arabidopsis stomatal closure (Col-0; Fig.…”
Section: Gork Acts As the Downstream Target Of Hrw Signalingmentioning
confidence: 99%
“…For example, hydrogen dissolved in Dulbecco's modified Eagle's medium was found to react with cytotoxic ROS and thus protect against oxidative damage in PC12 cells and rats (Ohsawa et al, 2007). The neuroprotective effect of H 2 -loaded eye drops on retinal ischemia-reperfusion injury was also reported (Oharazawa et al, 2010). In plants, corresponding results by using HRW combined with gas chromatography (GC) revealed that H 2 could act as a novel beneficial gaseous molecule in plant responses against salinity (Xie et al, 2012;Xu et al, 2013), cadmium stress , and paraquat toxicity (Jin et al, 2013).…”
mentioning
confidence: 96%
“…Thereafter, accumulating evidence from animal studies indicated a protective effect of H 2 pretreatment on the progression of organ damage in various types of disease models , such as ischemia-induced injury and dysfunction of the brain [22,33,39,55,59,[62][63][64], heart [34,45,59,65], liver [30], retina [41], and kidney [59,60]; stress-induced hippocampus dysfunction [38]; cisplatinum nephropathy [37,44]; transplanted intestinal graft [31,47]; corneal alkali burn [51]; ouabain-induced auditory neuropathy [66]; lung injury by oxygen toxicity [43,46]; paraquat [52]; extensive burns [54]; chronic allograft nephropathy [48]; and radiation injuries in various organs [49,50,55,68,69]. In Parkinson's disease [36,40] and Alzheimer's disease models [42], H 2 ameliorates neurodegenerative changes in the brain.…”
Section: The Hydrogen Gas Molecule As a Biological Antioxidantmentioning
confidence: 99%
“…In 2010, Oharazawa et al dissolved H 2 in saline as H 2 loaded eye drops and found that it could ameliorate ischemia-reperfusion injury of the retina in a rat model by administering it to the ocular surface (Oharazawa et al, 2010). In 2011, Kubota used it to prevent oxidative stress-induced angiogenesis in a mouse corneal alkali-burn model with great success (Kubota et al, 2011).…”
Section: H 2 -Loaded Eye Drops and Hydrogen Bathmentioning
confidence: 99%
“…Soon afterwards H 2 was found to be effective for many other diseases, including hepatic and cardiac hypoxia-ischemia injury, inflammation injury caused by small intestine transplantation, neonatal hypoxia-ischemia injury, and lung allograft, (Fukuda et al, 2007;Buchholz et al, 2008;Cai et al, 2008;Hayashida et al, 2008;Kawamura et al, 2011;). Besides, other ways to administrate H 2 , such as drinking H 2 -saturated water, intraperitoneal and intravenous injection of H 2 -saturated saline (first developed by our group), have also been proved to be effective to many disorders related with oxidative stress, such as cerebral hypoxia-ischemia injury, human typeⅡ diabetes, nephrotoxicity induced by cisplatin, Parkinson's disease and atherosclerosis in apolipoprotein Chen et al, 2009;Mao et al, 2009;Zheng et al, 2009;Oharazawa et al, 2010). Up to now, H 2 has been proved to be effective to various disease models.…”
Section: Introductionmentioning
confidence: 96%